2021
DOI: 10.3390/insects12040337
|View full text |Cite
|
Sign up to set email alerts
|

Pupation Substrate Type and Volume Affect Pupation, Quality Parameters and Production Costs of a Reproductive Colony of Ceratitis capitata (Diptera: Tephritidae) VIENNA 8 Genetic Sexing Strain

Abstract: Adequate pupation substrates and substrate volume are critical factors in the mass-rearing of insects for Sterile Insect Technique (SIT) applications. To identify an ideal pupation substrate for a reproductive colony of Ceratitis capitata (Wiedemann) VIENNA 8 genetic sexing strain, we first examined pupation in cellulose from recycled paper (cellulose I), sawdust, fine wheat bran, vermiculite and coconut fiber using a volume of 2.5–12.5 mL of substrate for each 5 mL volume of fly larvae. We found a positive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Pascacio-Villafán and colleagues (2021) also tested different pupation substrates and substrate volumes for the Mediterranean fruit fly Ceratitis capitata VIENNA 8 genetic sexing strain (GSS) that is currently used by almost all operational SIT programs against this major agricultural pest worldwide [ 7 ]. They concluded that cellulose III at low volumes is the best pupation substrate, with respect to productivity, quality and cost-effectiveness.…”
Section: Fruit Fliesmentioning
confidence: 99%
“…Pascacio-Villafán and colleagues (2021) also tested different pupation substrates and substrate volumes for the Mediterranean fruit fly Ceratitis capitata VIENNA 8 genetic sexing strain (GSS) that is currently used by almost all operational SIT programs against this major agricultural pest worldwide [ 7 ]. They concluded that cellulose III at low volumes is the best pupation substrate, with respect to productivity, quality and cost-effectiveness.…”
Section: Fruit Fliesmentioning
confidence: 99%
“…SIT works by releasing radiation-sterilized males to an existing population, to mate with wild females so that they have no viable o spring [11,12]. SIT has been successfully applied in the control of several agricultural pests such as invasive fruit ies, lepidopteran, and Hemiptera [13][14][15][16][17]; however, it has a limited ability to control mosquitoes due to the three issues. (1) It requires introducing large quantities of sterile mosquitoes.…”
Section: Introductionmentioning
confidence: 99%